Energy literacy assessment among Portuguese university members: Knowledge, attitude, and behavior. (December 2020) - Martins, Ana; Madaleno, Mara; Dias, Marta Ferreira
Abstract: Energy literacy is a useful tool that allows consumers to acquire the knowledge, desire, availability, and obliges to a personal commitment necessary for more efficient energy management. Knowledge about energy, the ability to perform financial calculations, attitude and behavior, all together allows evaluating the different aspects in which it may be necessary to intervene to make people more aware of the need to save energy and more available and receptive to change their energy consumption habits. Using Principal Component Analysis (PCA) we aim to create an energy literacy index, as well as the indices for each of the energy literacy dimensions and to determine which factors influence energy literacy levels. The results obtained allowed us to confirm the influence of gender in energy literacy, verifying that, although women have less knowledge, they demonstrate a more positive attitude and more correct behavior.